Potential producers of biogenic magnetic nanoparticles among disease-producing microorganisms of the brain - Gorobets, S.V.; Gorobets, O.Yu.; Darmenko, Y.A. (Functional Materials, 2017)
In this paper, microorganisms-causative agents of brain disease have the potential to produce biogenic magnetic nanoparticles (BMN), which can accumulate in the human brain in addition to BMN, which are biomineralized in the human brain. The BMN of these microorganisms can attract particular interest for the manufacture of magnetic nanoparticles as functional materials of a wide range of applications such as nanoelectronics, targeted delivery of drugs and a contrast agent for magnetic resonance imaging.